Automated Tube Voltage Selection in Thoracoabdominal Computed Tomography at High Pitch Using a Third-Generation Dual-Source Scanner: Image Quality and Radiation Dose Performance. Issue 5 (May 2015) - Lurz, Markus; Lell, Michael M.; Wuest, Wolfgang; Eller, Achim; Scharf, Michael; Uder, Michael; May, Matthias Stefan
Abstract : Objectives: The objective of this study was to evaluate the radiation dose and image quality performance of thoracoabdominal examinations with an automated tube voltage selection (tube voltage adaptation), tube current modulation, and high pitch using a third-generation dual-source computed tomography (CT) compared intraindividually with 120-kV examinations with tube current modulation with special attention on clinically relevant lesions in the liver, the lungs, and extrahepatic soft tissues. Materials and Methods: This study was approved by the institutional review board. Computed tomography of the body was performed using a third-generation dual-source system in 95 patients (mean body mass index, 25 kg/m 2 ; range, 18–35 kg/m 2 ). For 49 of these patients, all calculated tube settings and resulting dose values were recorded for each of the 12 gradual contrast weightings of the tube voltage adaptation algorithm. Spiral CT was performed for all patients with an intermediate weighting (grade 7) in a portal venous phase at 120 reference kV, 180 reference mAs, and pitch of 1.55. Objective image quality was assessed on the basis of contrast-to-noise ratio. Subjective image quality was assessed on the basis of clarity and sharpness of anatomical and pathological structures as well as interfering beam hardening and spiral and motion artifacts (heart, lungs, diaphragm). Previous examinations on a 64-slice scanner served as reference. Results: All examinations were rated good or excellent for clinical diagnosis. Automated tube voltage selection resulted in significantly lower effective radiation dose (9.5 mSv) compared with the reference (12.0 mSv; P < 0.01). Contrast-to-noise ratio and image quality of soft tissue lesions were significantly increased ( P < 0.01). Motion artifacts were significantly reduced ( P < 0.01). Conclusions: Automated tube voltage adaptation combined with high-pitch protocols allows for a substantial radiation dose reduction while substantially increasing the image quality, even at large-volume exposure.